Analisis Kesalahan Kakujoshi ﻿pada ﻿Sakubun ﻿Mahasiswa Program Studi Pendidikan Bahasa Jepang Universitas Negeri Padang - lestari, suci islamiah; Yulia, Nova (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2024)
This study aims to determine the error of using kakujoshi in the pocketbun of students of the Class of 2019 of the Japanese Language Education Study program. The theory used in this study is the kakujoshi function theory of T.Chandra and Chino with a type of qualitative research using the descriptive method of analysis. The source of data is the pocketbun of students of the Class of 2019 with 30 respondents. The highest error is found in kakujoshi de as many as 10 errors, and the lowest error is found in kakujoshi ya which is as many as 1 error. Researchers analyze based on the type of error with discussion based on a syntactic point of view.